Impact of SFDP Under ADB on Income Generation Activities at Bokhim VDC Bhojpur - Shrestha, Tirtha Kumar (Tribhuvan University Journal, 2011)
Available with full text Key words: Underdeveloped country; acute poverty; Low per capita income; Very low standard of life Tribhuvan University Journal Vol XXIII, No. 1, 2001 Page: 87-96 Uploaded date: 21 April, 2011